Charge-Mediated Pyrin Oligomerization Nucleates Antiviral IFI16 Sensing of Herpesvirus DNA - Krystal K. Lum (American Society for Microbiology, 2019)
ABSTRACT The formation of multimerized protein assemblies has emerged as a core component of immune signal amplification, yet the biochemical basis of this phenomenon remains unclear for many mammalian proteins within host defense pathways. The interferon-inducible protein 16 (IFI16) is a viral DNA sensor that oligomerizes upon binding to nuclear viral DNA and induces downstream antiviral responses. Here, we identify the pyrin domain (PYD) residues that mediate IFI16 oligomerization in a charge-dependent manner. Based on structure modeling, these residues are predicted to be surface exposed within distinct α-helices. By generating oligomerization-deficient mutants, we demonstrate that IFI16 homotypic clustering is necessary for its assembly onto parental viral genomes at the nuclear periphery upon herpes simplex virus 1 (HSV-1) infection. Preventing oligomerization severely hampered the capacity of IFI16 to induce antiviral cytokine expression, suppress viral protein levels, and restrict viral progeny production. Restoring oligomerization via residue-specific charge mimics partially rescued IFI16 antiviral roles. We show that pyrin domains from PYHIN proteins are functionally interchangeable, facilitating cooperative assembly with the IFI16 HINs, highlighting an inherent role for pyrin domains in antiviral response. Using immunoaffinity purification and targeted mass spectrometry, we establish that oligomerization promotes IFI16 interactions with proteins involved in transcriptional regulation, including PAF1C, UBTF, and ND10 bodies. We further discover PAF1C as an HSV-1 restriction factor. Altogether, our study uncovers intrinsic properties that govern IFI16 oligomerization, which serves as a signal amplification platform to activate innate immune responses and to recruit transcriptional regulatory proteins that suppress HSV-1 replication. IMPORTANCE The ability of mammalian cells to detect the genomes of nuclear-replicating viruses via cellular DNA sensors is fundamental to innate immunity. Recently, mounting evidence is supporting the universal role of polymerization in these host defense factors as a signal amplification strategy. Yet, what has remained unclear are the intrinsic properties that govern their immune signal transmission. Here, we uncover the biochemical basis for oligomerization of the nuclear DNA sensor, IFI16. Upon infection with herpes simplex virus 1 (HSV-1) in human fibroblasts, we characterize the contribution of IFI16 oligomerization to downstream protein interactions and antiviral functions, including cytokine induction and suppression of HSV-1 replication. Until now, the global characterization of oligomerization-dependent protein interactions for an immune receptor has never been explored. Our integrative quantitative proteomics, molecular CRISPR/Cas9-based assays, mutational analyses, and confocal microscopy shed light on the dynamics of immune signaling cascades activated against pathogens.